Cross-Cultural and Religious Critiques of Informed Consent - Tham, Joseph; Gómez, Alberto García; Garasic, Mirko Daniel (Routledge Focus on Religion, 2022)
This book explores the challenges of informed consent in medical intervention and research ethics, considering the global reality of multiculturalism and religious diversity. Even though informed consent is a gold standard in research ethics, its theoretical foundation is based on the conception of individual subjects making autonomous decisions. There is a need to reconsider autonomy as relational-where family members, community and religious leaders can play an important part in the consent process. The volume re-evaluates informed consent in multicultural contexts and features perspectives from Buddhism, Confucianism, Hinduism, Christianity, Judaism and Islam. It is valuable reading for scholars interested in bioethics, healthcare ethics, research ethics, comparative religions, theology, human rights, law and sociology.